1011. Sepsis and Secondary Hemophagocytic Lymphohistiocytosis. (26th November 2018) - Fazal, Farhan; Wig, Naveet; Soneja, Manish; Mitra, Dipendra K; Panda, Sk; Satpathy, Gita; Vikram, Naval Kishore; Pandey, R M; Chaturvedi, P K
Abstract: Background: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory condition diagnosed by HLH 2004 criteria. This criterion has common clinical and laboratory features with sepsis and tropical fevers, but there is marked difference in management and outcome of these two entities. The study is conducted to know whether there is any difference in the clinico-laboratory features, management, and outcome of sepsis with or without secondary HLH. Methods: This is a prospective observational study where patients presenting with sepsis and bicytopenia are included. The patients underwent relevant investigations according to 2004 HLH diagnostic criteria. The patients are divided into sepsis with or without HLH. The underlying etiology, treatment, and outcome of the two groups are analysed. Results: Fifty sepsis patients are included in the study, out of which 28 fulfilled the HLH diagnostic criteria which comprised of 18 men and 10 women. The etiology were bacterial (three enteric fever, three tuberculosis, two scrub typhus, one Staphylococcal aureus ), viral (one dengue fever, two HIV, two encephalitis), fungal (one aspergillosis, one mucormycosis, two others), parasites (three malaria, one leishmania) malignancy (two hodgkin lymphoma, one non-Hodgkins lymphoma), and unknown etiology in six patients, with >1 etiology in three patients (Figure 2). The percentage of each criterion fulfilled in both groups is given in Figure 1, showing an increased occurrence of splenomegaly, low NK cell activity, hypertriglyceridemia in HLH patients. Steroids along with supportive treatment was given to 53% and etoposide was added in 7%. Treatment for underlying etiology alone without immunosuppressive treatment was given in 39%. The mortality in those with HLH vs. without HLH was 42% and 31%, respectively. The median duration of hospital stay was 18 and 36 days in HLH and without HLH group, respectively. Conclusion: HLH should be suspected in sepsis patients with bicytopenia specially in tropical fevers. There is increased mortality if the sepsis patients fulfil HLH criteria. Early diagnosis and management is of paramount importance. Disclosures: All authors: No reported disclosures.